Security Techniques Against Power Exhausting Attacks in WSN: A Fundamental Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
DoS attack is being considered for the wireless sensor network, where the attack affects the battery life of the devices connected in the network. The basic goal of the DoS attack is just to reduce the availability of the necessary devices connected by reducing the battery lifetime. The connected devices are kept on unnecessary use which results in the reduction of the battery life and effects the battery management. In the proposed work, a novel methodology shall be taken for the better management of the battery lifetime of the devices connected. In case if any of the connected devices detects low power or when not in use, it goes to sleep mode for the better usage of the battery power. In the discussed methodology the system is made prone to such type of attacks and also works for the detection of such types of attacks and nodes too. In the work presented the major consideration is for the explanation and in-depth knowledge about the domain and specially for the energy exhausting attacks and techniques. On the basis of the survey considered a specific problem is being considered in the work for which a tentative solution is also provided with the points that are to be considered for the evaluation of the work. In the proposed methodology RSSI value along with information of the route is being used for the discernment of the malicious nodes and for ensuring the security of the network, the cluster mechanism is being considered for the better and improved results. The enhancement in the previous work is being done for the better power management.